2013
DOI: 10.1364/oe.21.013656
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and multi-species measurements by supercontinuum absorption spectroscopy for IC engine applications

Abstract: Abstract:The first supercontinuum (SC) absorption spectroscopy measurements showing the feasibility of quantitative temperature evaluation are presented to the best of the authors' knowledge. Temperature and multi-species measurements were carried out at a detection rate of ∼2 MHz in a high-temperature flow cell within a temperature range from 450 K to 750 K at 0.22 MPa, representing conditions during the suction and compression stroke in an internal combustion (IC) engine. The broadband SC pulses were tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Although studies have shown promise, the restriction to the near-infrared wavelength region, as well as the inherent shot-to-shot fluctuations, reduces the SNR. This demands considerable bin-averages in excess of 1000 pulses, as seen in the work of Sanders [18] and Werblinski et al [19], consequently compromising effective time resolutions of such sensors to well below 50 kHz. The typical chirp rates in these supercontinuum lasers are four orders of magnitude larger than that of chirped semiconductor lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies have shown promise, the restriction to the near-infrared wavelength region, as well as the inherent shot-to-shot fluctuations, reduces the SNR. This demands considerable bin-averages in excess of 1000 pulses, as seen in the work of Sanders [18] and Werblinski et al [19], consequently compromising effective time resolutions of such sensors to well below 50 kHz. The typical chirp rates in these supercontinuum lasers are four orders of magnitude larger than that of chirped semiconductor lasers.…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the generation of SC radiation and its use in chemical sensing including the detection of typical fuel molecules was given by Kaminski et al [135]. So far, most work using SC absorption spectroscopy focused on sensing selected species such as water, carbon dioxide and small hydrocarbons in the gas phase, see for example [135][136][137][138][139]. However, future developments in this area may lead to methods for comprehensive fuel characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significant improvement on the temperature sensitivity can be realized by scanning the wavelength over multiple absorption transitions. The broad spectral coverage facilitates the optimization of the sensitivity in different temperature ranges and used to be fitted against spectral databases for determination of combustion parameters (48,81,82).…”
Section: Selection Of Absorption Transitions and Realizationmentioning
confidence: 99%
“…The laser sources could perform better with customized designs for specific applications. Nowadays, the tunable laser sources are compact, reliable and relatively cheap, and thus make LAS widely applied to combustion diagnosis in various areas, such as engines monitoring and design (43,(48)(49)(50)(51), gas phase analysis in shock tubes (52)(53)(54)(55) and power plant exhaust monitoring (56)(57)(58).…”
Section: Introductionmentioning
confidence: 99%